GRANULAR ENRICHED-COMPOST FROM ORGANIC WASTE CAMPUS AS SOIL CONDITIONER IN INTENNSIVE RICE FARMING SYSTEM - Azizah, Nur; Prasetya, Budi; Kurniawan, Syahrul (AGRIVITA Journal of Agricultural Science, 2013)
Effort to reduce the high dependence of farmers on inorganic fertilizers is introducing compost as soil conditioner. The objectives of this research are to create enriched granular-compost (EGC) and to test its effect on nutrient availability, plant growth, and grain yield in intensive farming systems. The research was conducted in two consecutive years (2011-2012), consisting of three steps: production of EGC, incubation and field experiment. Incubation experiment was designed by randomized complete design with 5 treatments (control, 4, 6, 8, and 12 Mg ha-1), and the design of field experiment was randomized block design with 7 treatments (control, inorganic fertilizer (IF), 25% EGC + 75% IF, 50% EGC + 50% IF, 75% EGC + 25% IF, 100% EGC + 100% IF and 100% EGC). The results showed that application of EGC increased total-N and P-available 12.5% and 33% respectively on the 10th day after incubation. The highest grain yield (6.13 Mg ha-1) was gained from the application of 100% EGC + 100% IF. The productivity of rice is closely related to the number of productive panicles per plant (r = 0.507*) and percent of filled grain (r = 0.685*).  Keywords: enriched granular-compost, nutrient availability, grain yield